Endoscopic mucosal resection/endoscopic submucosal dissection for gastric heterotopic pancreas - Yun-Shi ZHONG,; Qiang SHI,; Li-Qing YAO,; Ping-Hong ZHOU,; Mei-Dong XU,; Ping WANG, (Turkish Journal of Gastroenterology, 2019)
-